2008
DOI: 10.1007/s11104-008-9748-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of a layered double hydroxide (LDH) to buffer nitrate in soil: long-term nitrate exchange properties under cropping and fallow conditions

Abstract: The potential use of a layered double hydroxide (LDH) to act as a nitrate buffer system in soil in order to reduce the movement of nitrate was investigated. Long-term plant and soil experiments were carried out under greenhouse conditions with the following objectives: (i) evaluate the nitrate adsorption capacity of the LDH during crop growth, and its influence on N uptake, (ii) study the ability of the LDH to adsorb nitrate mineralized during fallow periods, and its influence on nitrate leaching, (iii) evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 28 publications
(36 reference statements)
0
15
0
4
Order By: Relevance
“…(Komarneni et al, 1996;De Roy et al, 2001;Khan and O'Hare, 2002) even at room temperature. Since LDH has positive charges on a layer surface and thus could be used as a nitrate carrier or for controlled nitrate release for agricultural uses, several studies have been conducted for nitrate ion release characteristics to check the feasibility of LDH as the slow release fertilizer (Komarneni et al, 2003;Gillman and Noble, 2005;Halajnia et al, 2013;Urena-Amate et al, 2011;Torres-Dorante et al, 2009). Komarneni et al (2003) carried out the experiment of nitrate release from several LDHs in simulated soil solutions and investigated the influences of the type of anions present in the soil solution, their concentration, and crystal size and charge density of LDHs.…”
Section: +mentioning
confidence: 99%
“…(Komarneni et al, 1996;De Roy et al, 2001;Khan and O'Hare, 2002) even at room temperature. Since LDH has positive charges on a layer surface and thus could be used as a nitrate carrier or for controlled nitrate release for agricultural uses, several studies have been conducted for nitrate ion release characteristics to check the feasibility of LDH as the slow release fertilizer (Komarneni et al, 2003;Gillman and Noble, 2005;Halajnia et al, 2013;Urena-Amate et al, 2011;Torres-Dorante et al, 2009). Komarneni et al (2003) carried out the experiment of nitrate release from several LDHs in simulated soil solutions and investigated the influences of the type of anions present in the soil solution, their concentration, and crystal size and charge density of LDHs.…”
Section: +mentioning
confidence: 99%
“…Samples were stored at -18°C prior to analysis. There is no problem of nitrite or nitrate sorption on soil particles since the anionic exchange capacity (AEC) is mainly developed in acidic tropical and sub-tropical soils with a high content of aluminium and iron hydroxides/oxides or in some volcanic ashes derived soils (Torres-Dorante et al 2009). These soils represent only 1% of the total soil surface of the globe (TorresDorante et al 2009).…”
Section: Potential Microbial Activitiesmentioning
confidence: 99%
“…Actually, some studies have reported the potential use of LDHs as adsorbents or reservoirs of nitrate. [9,10,[13][14][15][16][17][18] However, the selectivity of LDHs for nitrate is generally considered not to be high, and a large number of studies have reported that anions with a higher charge density tend to be more preferentially intercalated into LDHs. [6][7][8]19,20] According to a report by Miyata, [19] the order of exchange selectivity for monovalent anions in the case of Mg-Al LDHs (Mg/ Al = 2.3) is OH -> F -> Cl -> Br -> NO 3 -> I -, and according to a report by Costa et al, [20] the order of exchange selectivity based on a computational simulation with Zn-Al LDHs (Zn/Al = 2) is CO 3 2-> OH -> F -> Cl -> Br -> NO 3 -.…”
Section: Introductionmentioning
confidence: 99%